PIPE CONDITION ANALYSIS USING ULTRASONIC TESTING TO PREDICT THE REMAINING SERVICE LIVE (RSL) OF THE PETROLEUM DISTRIBUTION PIPELINE - Sarah Dampang; Nanang Burhan; Cindi Ramayanti (Universitas Lambung Mangkurat, 2019)
The pipeline network in the petroleum industry is very susceptible to corrosion. Corrosion problems can cause losses that are not small financially. Corrosion that occurs in underground pipes can be in the form of external corrosion on the outer surface of the pipe caused by acid content in the air or in the soil or internal corrosion inside the pipe caused by petroleum content in the form of water, carbon dioxide (CO2) and hydrogen sulfide (H2S). Corrosion causes the useful or service life of these pipes to be shorter than expected. This study aims to measure the Remaining Service Life (RSL) of the petroleum distribution pipeline as an initial step of preventive action to avoid fatal consequences of corrosion problems. In this study, ultrasonic testing was used as one of the Non Destructive Testing (NDT) methods to check the condition of the petroleum distribution pipe's wall. In this study, it is found that the Remaining Service Life (RSL) of the pipeline under investigation is 25 years.